Some Properties and Distribution of the Zeros of the q-Sigmoid Polynomials - Jung Yoog Kang (Discrete Dynamics in Nature and Society)
The sigmoid polynomials combining q-numbers and various properties of their polynomials are thoroughly presented in this paper. Based on several properties of q-numbers, we derive some identities of q-sigmoid polynomials. Also, from explicit polynomials, we can observe structures of the zeros of the sigmoid polynomials which are related to q-numbers.